Coagulase negative staphylococci from ovine bulk-tank milk: Effects of the exposure to sub-inhibitory concentrations of disinfectants for teat-dipping. (June 2021) - Marzoli, Filippo; Turchi, Barbara; Pedonese, Francesca; Torracca, Beatrice; Bertelloni, Fabrizio; Cilia, Giovanni; Cerri, Domenico; Fratini, Filippo
Highlights: Sub-inhibitory exposure to disinfectants increased disinfectant resistance in CoNS. Disinfectant resistance increase was not dependent on qac gene presence. Antibiotic resistance was affected by sub-inhibitory exposure to disinfectants. Biofilm production was not affected by sub-inhibitory exposure to disinfectants. Abstract: Teat-dipping is one of the most effective methods to prevent mammary infections in ruminants, including sub-clinical mastitis caused by coagulase-negative staphylococci (CoNS). Improper disinfectant application could expose microorganisms to sub-inhibitory concentrations leading to phenotypic variations. In this study, 12 chlorhexidine-digluconate (CHDG)-tolerant (of which 4 qac positive) and 12 benzalkonium chloride (BC)-tolerant (of which 7 qac -positive) CoNS isolates from ovine milk were exposed to sub-inhibitory concentrations of CHDG and BC, respectively. Changes in disinfectant susceptibility against BC and CHDG, antibiotic resistance against 12 antibiotics and biofilm production were then assessed for both groups. After CHDG stress, 67 % and 83 % of the CHDG-stressed isolates doubled their MICs for BC and CHDG, respectively and 2 qac -negative isolates showed a four-fold increase of their MBCs for CHDG. After BC stress, MICs for BC and CHDG doubled in 58 % and 83 % of the BC-stressed isolates, respectively, while one qac -positive isolate increased four-fold the MIC for BC. Cross-resistance to antibiotics was assessed by disc diffusion method. Some qac -positive isolates varied their resistance profile, while a blaZ -positive isolate showed a resistant phenotype against ampicillin only after the exposure to the disinfectant. As for qac -positive isolates, one CHDG-stressed and 2 BC-stressed increased their resistance to kanamycin and cefoxitin, respectively. The Congo Red Agar test was carried out to assess the in vitro slime production: all isolates were negative after stress. In conclusion, sub-inhibitory exposure to disinfectants may affect disinfectant and antibiotic susceptibility, the latter in particular for qac -positive isolates and those hosting unexpressed antibiotic resistance genes.